Pengaruh Persepsi Return dan Risiko terhadap Minat Berinvestasi Saham di Pasar Modal: Studi Kasus pada Mahasiswa Program Studi Manajemen Universitas Teuku Umar - Hadisah, Hadisah; Mandaraira, Fitria; Muzakir, Muzakir (Regress: Journal of Economics & Management, 2025)
This study aims to examine the impact of return perception and risk perception on stock investment interest in the capital market, using a case study of Management students at Universitas Teuku Umar. The research employs a quantitative correlational approach. The sampling technique used is non-probability sampling known as accidental sampling. The population and sample were determined using the Slovin formula, resulting in 100 Management students from Universitas Teuku Umar as respondents. Data was collected through questionnaire distribution. Data analysis was performed using multiple linear regression with SPSS V.26 software. The findings indicate that return perception (X1) has a significant partial effect on investment interest (Y), with a significance value of 0.000 < 0.05. Risk perception (X2) has no significant partial effect on investment interest (Y), with a significance value of 0.570 > 0.05. Both return perception (X1) and risk perception (X2) have a significant simultaneous effect on investment interest (Y), with a significance value of 0.000 < 0.05. Return perception (X1) and risk perception (X2) can explain 71.4% of the variance in investment interest (Y) and contribute 49.9% to the variance in investment interest (Y). The remaining 50.1% is influenced by factors not included in this study, such as psychological factors, knowledge level, information about the capital market, individual risk tolerance, and previous investment experience, which could be considered for future research.